ANALISA PROSES AUDIT SISTEM INFORMASI BIRO MANAJEMEN ASSET DAN LOGISTIK MENGGUNAKAN FRAMEWORK COBIT 4.1. PADA INSTITUT INFORMATIKA DAN BISNIS DARMAJAYA BANDAR LAMPUNG - Amnah - (Jurnal Informatika, 2014)
In order to ensure the audit performed well and appropriate, it is important to analyses every stage of the audit process. This analysis is intended to find out whether the maximum goal of organization is achieved or not. Also, the further development, if needed, by adding elements of assessment to increase the quality of each section of organization, in this case, Asset Management and Logistics Bureau of IBI Darmajaya. Asset Management and Logistics Bureau of IBI Darmajaya is in charge of procuring and maintenance of assets in IBI Darmajaya Lampung is the bureau in charge of procuring, maintaining and securing the assets that exist in the IBI Darmajaya, there in Biro Information Systems Asset management and Logistics is important in the service provider for all users and management, which is expected to improve the performance and quality of service. Questions that begin with whether the services provided by the Bureau of Asset Management and Logistics has directed and aligned with business objectives Institutions, whether the use of COBIT 4.1 Domain. Has been right on target or still can be improved further. This analysis process produces findings , the level of alignment between IT objectives and the Institution has been reached and is in Defined level because the average IT processes have been above the level of the international standard of 2.5 (Gulden tops , 2000 ) While the average IT has exceeded the standard international but still can be improved by adding domain relevant to the process undertaken , in order to improve the alignment between in objectives and Purpose Institutions towards a higher level , domain-related is PO5, PO7, AI2, and ME2, with the addition of this domain can generate data more better, so that management can take steps or actions more effective.Keywords: Maturity Level, Information Systems, Asset Management, COBIT